Mewujudkan Kopi Cinangka sebagai Produk Unggulan dengan Perlindungan Indikasi Geografis di Kabupaten Serang - Dwisvimiar, Inge; Khairunnisa, Hafifa (Universitas Serang Raya, 2023)
Serang Regency is one of the areas that does not yet have registered Geographical Indication products, although there are many natural potentials, such as Cinangka coffee, that must be protected within the framework of Geographical Indications as a characteristic of agricultural products in Banten Province. The aim of the research is to identify opportunities for Cinangka coffee in Serang Regency based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications and efforts to realize Cinangka coffee as a superior product that has the potential to become a geographical indication in Serang Regency. This type of research is normative-empirical legal research; the focus of the study is on legal norms and the application of law in society. The sources of data used are secondary and primary data. The data analysis used is qualitative. The results of the study show that to identify opportunities for Cinangka coffee in Serang Regency, based on Law Number 20 of 2016, concerning Trademarks and Geographical Indications, it is necessary to use a book of requirements or a predetermined description document. In Article 6 paragraph (3) of Government Regulation on Geographical Indications Number 51 of 2007 and Regulation of Law and Human Rights Number 12 of 2019 concerning Geographical Indications, the Cinangka Coffee description document contains six points out of the ten required. Efforts to realize Cinangka coffee as a superior product include efforts by local governments through training, supervision, and the provision of production support tools, as well as community efforts, namely involving members of coffee producers in various programs launched by local governments to increase productivity and marketing, as well as introducing Cinangka coffee products to the wider community.